Wind and shadows; the story of Joan of Arc. - Daughters of St. Paul. ([Boston] St. Paul Editions, 1968)
A biography of Joan of Arc as she struggled to follow the commands of her "voices" and free France from the English.
Keywords: Joan, -- of Arc, Saint, -- 1412-1431 -- Juvenile literature; Joan, -- of Arc, Saint, -- 1412-1431.; Saints; Women -- Biography